Functionalization of Counseling of Prospective Brides : (Study of the Jekan Raya Religious Affairs Office, Palangka Raya City) - Hardiansyah, Fathoni; Erawati, Desi; Ariani, Anita; Apriatama, Dony; Akbar, Nadzmi (Amala Jurnal Pengabdian Kepada Masyarakat, 2022)
The urgency of getting marriage was to establish peace, blessing and the pleasure of God. Therefore, before the wedding carried out, the main steps needed to be prepared were the readiness of couple, the seriousness and the basic strength of marriage law. This paper investigated the role of pre-marital assistance or counseling of couples, using a service learning (SL) approach with several stages carried out. The result revealed that not all couples knew the functions and benefits of pre-marital counseling, and the importance of pre-marital guidance was to minimize divorce and reaffirmed the meaning of getting marriage in Islam. Pre-marriage guidance or counseling is a mandatory service given to the bride and groom, usually counseling given a week before the marriage contract is performed. Pre-marital guidance or counseling aims to reduce the number of divorces, which in the process the bride and groom are given useful supplies in front of him in building a household. Pre -marital guidance is considered important because the beginning of the household is highly dependent on the initial supply before the bride and groom are married and pre -marital guidance also aims to help the bride and groom in making mature planning associated with marriage and married life. Based on the results of pre-marital guidance or advice given that there is a change to the bride, this is evidenced when finished counseling, the bride is asked again about what has been obtained from the guidance done, the bride can re-elaborate important points which has been conveyed by the mentor until the intended target has been met, and it is hoped that in the future it can be useful and be a supply for the bride and groom.